2010
DOI: 10.1002/pc.20996
|View full text |Cite
|
Sign up to set email alerts
|

Matrix hybridization in the interlayer for carbon fiber reinforced composites

Abstract: Polymeric composites have gone through a level of maturity beyond the laboratory stage with the development of the Boeing 787, the structure of which contains more than 50% composites. Nonetheless, a basic understanding of the material used in its primary structure has not been extensively investigated. For instance, micromechanical models are inadequate as they always assume an evenly distributed homogeneous matrix, without following classic lamination theory, which assumes constant stress through the laminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…1 Many industrial sectors are adopting a variety of engineered nanomaterials (ENMs) for improved strength, weight, texture, biocidal and optical properties tailored to specific applications. 23 Examples of such NEPs include paint coatings, with a variety of submicron/nanoscale pigment (metal and oxide) powders; 4 toner formulations; 57 polymer- and carbon-matrix nanocomposites; 8 sintered compacts made of metal and oxide nanoparticles; 9 super hard coatings. 10 …”
Section: Introductionmentioning
confidence: 99%
“…1 Many industrial sectors are adopting a variety of engineered nanomaterials (ENMs) for improved strength, weight, texture, biocidal and optical properties tailored to specific applications. 23 Examples of such NEPs include paint coatings, with a variety of submicron/nanoscale pigment (metal and oxide) powders; 4 toner formulations; 57 polymer- and carbon-matrix nanocomposites; 8 sintered compacts made of metal and oxide nanoparticles; 9 super hard coatings. 10 …”
Section: Introductionmentioning
confidence: 99%
“…The number of consumer products containing ENPs is growing at a similarly rapid pace, and is expected to reach 10,000 by the year 2020 [3]. ENPs can be found in paint coatings with a variety of submicron/nanoscale pigment (metal and oxide) powders [4]; toner formulations [5]; polymer- and carbon-matrix nanocomposites with montmorillonite clays, carbon nanotubes and graphene [6]; and sunscreens/cosmoceuticals. Thus, human exposure to ENPs becomes inevitable and has indeed been demonstrated [7,8].…”
mentioning
confidence: 99%
“…In the case of impact tests carried out on woven CFRPs the absorbed energy was increased at the rate of 64% compared to the neat ones. Drakonakis et al [9] investigated the role of the host matrix and the micro-particle interleaving effect to the multilayer structures. From the three different matrices which were utilized, it was shown that the dicyanate was the toughest epoxy while the mode II fracture characteristics were considerably increased with the incorporation of Nylon 6 micro-particles.…”
mentioning
confidence: 99%